Organization and Implementation of Integrated Management System Processes - Cruise Port Dubrovnik - Vrdoljak Raguz, Ivona; Perucic, Doris; Pavlic, Ivana (International Review of Management and Marketing, 2012)
World cruise market is very dynamic and it is characterised by constant changes in offer and demand. Dubrovnik, as one of the leading port in the Mediterranean is faced with the problem of large concentrations of ships and passengers in a short period of time. Paper provides answers to the questions: how to manage cruise tourism in Dubrovnik? What are the guidelines for the further development of cruising in Dubrovnik? Modern ports management system must be organized and managed in a manner that will ensure the recognition requirements of stakeholders and their fulfilment. All this requires a more complex integrated management system, in which the requirements of quality management will be the basis, and requirements of environmental management needed an upgrade. Keywords: Cruise tourism; Dubrovnik; Management; Generic model of integrated management processes; Sustainable development JEL Classifications: M20